Achieving Competitive Advantage Through Internal Resources and Competences in the Financial Sector: A quantitative Study in Saudi Arabia - Ibrahim Alkandi (Communications of International Proceedings, 2024)
This study aims to explore how Saudi banks can utilize their resources and capabilities to achieve a competitive advantage. The resource-based approach has been applied to assess the resources and capabilities as well as how the management perceives these resources and capabilities sources of competitive advantages. A quantitative approach was implemented using cross-sectional data. The research population consisted of Top managers belong to Saudi’ banks, and the sample comprised 79 managers. The resources were sub divided into tangible and intangible resources. Among the variables that will be assessed in the research include propriety rights, trademark which is the brand, communication as well as banks’ culture. To achieve the objective of the research, Multivariate analysis through multiple regression was used. The research tool used is a questionnaire whose validity is also assessed. According to the results of the study, there is a significant relationship between bank’s performance and the strategic management of propriety rights, trademark, administrative and financial skills as well as bank culture. Therefore, the research assessed four aspects, among the variables in the model, in relation to the strategic performance of these banks. The aspects considered were trademark, communication, administrative and leadership style as well as the company’s culture. This paper contributes to the body of literature by providing empirical evidence of the resources influencing the banks’ market and economic performance.
Keywords: Strategic Management; business performance; Saudi Banks